Peningkatan Kepercayaan Diri Siswa Berbicara di Depan Kelas Melalui Layanan Bimbingan Kelompok Teknik Sosiodrama - Tiara Silvia; Hengki Yandri; Dosi Juliawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
This research is based on the phenomenon that there are still students who are not confident when performing in front of the class, so it negatively affects the development of student learning in school. The study aims to test the effectiveness of group guidance services with sociodramatic techniques in improving students' confidence in speaking in front of a class. This study uses a pre-experimental approach with the design of The One Group Pretest-Posttest Design. A total of 10 students of State Junior High School 4 Sungai Penuh who participated in group guidance activities with sociodrama techniques were selected through purposive sampling techniques and student confidence level data was revealed using a confidence scale that had been tested for validity and rehabilitation. Then the data that has been collected is analyzed using the Formula Wilcoxon Signed Ranks Test. The results revealed that group guidance services with sociodrama techniques are effectively used to improve their health.